The role of glucose homeostasis on immune function in response to exercise: The impact of low or higher energetic conditions - Von Ah Morano, Ana E. [UNESP]; Dorneles, Gilson P.; Peres, Alessandra; Lira, Fábio S. [UNESP] (Wiley, 2020)
Immune cells are bioenergetically expensive during activation, which requires tightly regulated control of metabolic pathways. Both low and high glycemic conditions can modulate immune function. States of undernourishment depress the immune system, and in the same way, excessive intake of nutrients, such as an obesity state, compromise its functioning. Multicellular organisms depend on two mechanisms to survive: the regulation and ability to store energy to prevent starvation and the ability to fight against infection. Synergic interactions between metabolism and immunity affect many systems underpinning human health. In a chronic way, the breakdown of glycemic homeostasis in the body can influence cells of the immune system and consequently contribute to the onset of diseases such as type II diabetes, obesity, Alzheimer's, and fat and lean mass loss. On the contrary, exercise, recognized as a primary strategy to control hyperglycemic disorders, also induces a coordinated immune-neuro-endocrine response that acutely modulates cardiovascular, respiratory, and muscle functions and the immune response to exercise is widely dependent on the intensity and volume that may affect an immunodepressive state. These altered immune responses induced by exercise are modulated through the “stress hormones” adrenaline and cortisol, which are a threat to leukocyte metabolism. In this context, carbohydrates appear to have a positive acute response as a strategy to prevent depression of the immune system by maintaining plasma glucose concentrations to meet the energy demand from all systems involved during strenuous exercises. Therefore, herein, we discuss the mechanisms through which exercise may promotes changes on glycemic homeostasis in the metabolism and how it affects immune cell functions under higher or lower glucose conditions.
Keywords: exercise training; glycemic homeostasis; immune cell functions